Optimizing the accession-level quantity of seeds to put into storage to minimize seed (gene)bank regeneration or re-collection - Hay, F.R.; Baum, K.J.; Oyatomi, O.; Wolkis, D. (Oxford University Press, 2025)
Seed (gene)banking is an effective way to conserve cultivated and wild plant diversity. However, long-term funding is not always consistently sufficient, and there is a need to both strengthen the effectiveness of genebank operations and maximize cost efficiency. One way to control the cost of maintaining a germplasm collection is to optimize the quantity of seeds per accession that is placed into storage, depending on the expected length of time a seed lot will remain above the viability threshold, expected rates of use for distribution and viability testing and on the requirement to ensure a reserve. Here, we express this as an equation, which can be applied to cultivated species and adjusted to different scenarios, but also to inform decisions about use of accessions of wild species where the number of seeds available is limited, a common scenario for wild-species conservation seed banks. For many crop genebanks, given the expected longevity of seeds, it would be worthwhile to increase the number of seeds produced and processed for storage. This would also help to diminish the risk of genetic drift due to frequent cycles of regeneration but would have implications in terms of how accessions are regenerated, in particular, how many plants are used for regeneration and the size of storage facilities. The equation we present can also be rearranged and used to plan how to allocate seeds for testing and use when the number of seeds available is limited. This may have particular relevance for species conservation seed banks.